PARANEOPLASTIC SYNDROMES - Suega, Ketut (journal of internal medicine, 2011)
The term Paraneoplastic Syndromes (PNS) refers to symptoms or signs resulting from damage to organs or tissuesthat are remote from the site of a malignant neoplasm or its metastases. Widely known examples include cancer cachexia,hypercalcemia,Cushing!s syndrome,and Trousseau!s syndrome . A particularly devastating form of paraneoplastic syndromes ia agroup of disorders classiÞ ed as Paraneoplastic Neurological Disorders (PND).The incidence of PNS varies with the neurologicalsyndrome and with the tumor. PNS can occurs in 7 to 10% of all patients with cancer. A paraneoplastic syndrome may resultfrom production and release of antibodies and physiologically active substances, or it may be idiopathic. However, not allparaneoplastic syndromes are associated with these antibodies. Symptoms can be atypical, psychiatric, or even ß uctuating,and PNS should often be in the differential diagnosis of otherwise unexplained neurological syndromes. An internationalpanel of neurologists has established diagnostic criteria that divide patients with a suspected PNS into deÞ nite and probablecategories. These criteria are based on the presence or absence of cancer, the presence of well-characterized antibodies, and thetype of clinical syndrome. Detection of a